2019
DOI: 10.1177/0961203319866506
|View full text |Cite
|
Sign up to set email alerts
|

One-decade study of distinct features, morbidity and mortality of systemic lupus erythematosus (an update on systemic lupus erythematosus in the Fars Province of Iran)

Abstract: Objective The objective of this article is to investigate the distinct features, morbidity and mortality of systemic lupus erythematosus (SLE) patients registered in rheumatology tertiary centers of Shiraz University of Medical Sciences from 2008 to 2018. Method A cross-sectional study was conducted on registered patients by reviewing their medical records. The clinical presentations were classified based on each organ’s distinct involvement. Result Data of 1322 patients with a mean age of 40 at the time of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 31 publications
2
4
0
Order By: Relevance
“…This is a survival study of an inception cohort of SLE patients diagnosed since 1995. Our results showed that the overall 10-year survival of our SLE patients was 92.9%, which is similar to those reported in Asian studies after the 2000s ( 9 11 , 16 , 18 , 21 , 24 ). However, direct comparison is not feasible because the cumulative survival rate computed by the Kaplan–Meier method was not reported in most of these studies.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This is a survival study of an inception cohort of SLE patients diagnosed since 1995. Our results showed that the overall 10-year survival of our SLE patients was 92.9%, which is similar to those reported in Asian studies after the 2000s ( 9 11 , 16 , 18 , 21 , 24 ). However, direct comparison is not feasible because the cumulative survival rate computed by the Kaplan–Meier method was not reported in most of these studies.…”
Section: Discussionsupporting
confidence: 90%
“…Although there have been a number of survival studies of SLE in the past decade, not too many were performed in the Asian populations (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25). Analysis of the survival of hospitalized patients (9,22), those admitted to the intensive care unit (12,19) or referred to tertiary centers (23), subsets of patients with nephritis (14), neuropsychiatric manifestations (17), or pulmonary hypertension (15) in some studies would create bias in the mortality rate.…”
Section: Introductionmentioning
confidence: 99%
“…This data is in line with several recent studies that evaluated main causes of hospitalizations throughout long period of follow-up. 27,28 On the other hand, as expected, hospital admissions related to other causes has been growing over the 10 years of follow-up; among these around 14% was due to infections.…”
Section: Discussionsupporting
confidence: 53%
“…In addition, the drug inhibits the proliferation of connective tissue, controls the permeability of cell membranes, and reduces severe exudation, thereby suppressing the immune response and reducing the inflammatory response. However, it has been clinically found that the therapeutic effect of prednisone when used as a single drug, is poor, while the addition of immunosuppressive therapy effectively improves clinical efficacy [14,15]. Cyclophosphamide, a clinically potent immunosuppressant, acts as an antiinflammatory agent by effectively blocking the release of cytokines.…”
Section: Discussionmentioning
confidence: 99%